2018
DOI: 10.1111/hae.13597
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the thrombin generation profiles of four different rFVIII products in FVIII‐deficient plasma using FIXa and FXIa activation

Abstract: Both FIXa- and FXIa activation results in similar TGA profiles across a FVIII range of 0.1%-33%; however, FIXa activation was more robust at the lowest levels of FVIII compared with FXIa activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…When performing a specific TG assay in a research setting, other activators such as factor IXa (FIXa) or factor XIa (FXIa) can be used, for example, when measuring factor VIII (FVIII) levels under 1%. 50,51 For the use of an in-house TF trigger, the source and concentration should be stated to indicate whether a low or high TF concentration is being used as a low TF predominantly activates the intrinsic coagulation pathway via factor IX (FIX), while a high TF mainly activates the extrinsic pathway via factor VIIa (FVIIa). When using in-house manufactured phospholipids, it is recommended to use the standard composition of 1,2-dioleoyl-sn-glycero-3-phosphose rine, 1,2-dioleoyl-sn-glycero-3-phosphoetanolamine, and 1,2-diol eoyl-sn-glycero-3-phosphocholine in the proportion of 20/20/60 (PS-PE-PC; 20%-20%-60%) at a final concentration of 1 or 4 µM, depending on the application.…”
Section: Reagent Concentrations and Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…When performing a specific TG assay in a research setting, other activators such as factor IXa (FIXa) or factor XIa (FXIa) can be used, for example, when measuring factor VIII (FVIII) levels under 1%. 50,51 For the use of an in-house TF trigger, the source and concentration should be stated to indicate whether a low or high TF concentration is being used as a low TF predominantly activates the intrinsic coagulation pathway via factor IX (FIX), while a high TF mainly activates the extrinsic pathway via factor VIIa (FVIIa). When using in-house manufactured phospholipids, it is recommended to use the standard composition of 1,2-dioleoyl-sn-glycero-3-phosphose rine, 1,2-dioleoyl-sn-glycero-3-phosphoetanolamine, and 1,2-diol eoyl-sn-glycero-3-phosphocholine in the proportion of 20/20/60 (PS-PE-PC; 20%-20%-60%) at a final concentration of 1 or 4 µM, depending on the application.…”
Section: Reagent Concentrations and Sourcesmentioning
confidence: 99%
“…In such cases, the CLSI guidelines for coagulation tests could be used as a directive. When performing a specific TG assay in a research setting, other activators such as factor IXa (FIXa) or factor XIa (FXIa) can be used, for example, when measuring factor VIII (FVIII) levels under 1% 50,51 . For the use of an in‐house TF trigger, the source and concentration should be stated to indicate whether a low or high TF concentration is being used as a low TF predominantly activates the intrinsic coagulation pathway via factor IX (FIX), while a high TF mainly activates the extrinsic pathway via factor VIIa (FVIIa).…”
Section: Analytical and Post‐analytical Factorsmentioning
confidence: 99%
“…Two papers published in Haemophilia explored the use of the TG assay to monitoring patient-specific factor replacement therapy. 2,3 The first study 2 defined individualized 'target' factor levels for FVIII or FIX therapies as a dose of spiked factor product, which brings the TG of plasma from the patient to that of a healthy individual.…”
Section: Thrombin Generation Assay Modifications Needed For Its Applimentioning
confidence: 99%
“…Surprisingly, only a few studies demonstrated that reduced TG correlates with increased bleeding in haemophilia. 4 In addition, commercial TG assay kits, such as Calibrated Automated Thrombogram (CAT, Stago), 2,3 are not very reliable at discerning the level of factor deficiency. Analysis of large sample sizes often demonstrates overlap of assay results from haemophilic patients and healthy volunteers, suggesting that the CAT assay may fail as a diagnostic tool.…”
Section: Thrombin Generation Assay Modifications Needed For Its Application To Monitoring Of Replacement Therapy For Haemophiliamentioning
confidence: 99%
See 1 more Smart Citation